Sequencing of the ART4 gene in sub‐Saharan cohorts reveals ethnic differences and two new DO alleles: DO*B‐Ile5Thr and DO*B‐Trp266Arg. Issue 10 (18th May 2015) - Durousseau de Coulgeans, Cécile; Chiaroni, Jacques; Bailly, Pascal; Chapel‐Fernandes, Sylvie
<x xml:space="preserve">Abstract</x> BACKGROUND Given the high heterogeneity of sub‐Saharan populations especially between nonpygmoids and pygmoids, differences are expected during investigation of the DO/ART4 gene. STUDY DESIGN AND METHODS Using genomic DNA extracted from blood samples collected from 77 Tswa pygmoids and 39 Teke and seven San nonpygmoids, DO coding regions were amplified and sequenced. A tetra‐primer amplification refractory mutation system‐polymerase chain reaction method was developed to specifically detect the DO*B‐SH‐Gln149Lys variant. Membrane expression of newly identified variant alleles in K562‐transduced cells was studied by flow cytometry. RESULTS Extensive polymorphism was confirmed in Teke or San nonpygmoids and Tswa pygmoids with, respectively, 12, zero, and 24 DO*A; 54, 10, and 115 DO*B or DO*B‐WL; five, zero, and 14 DO*HY; and six DO*JO alleles in Teke only. The DO*B‐SH‐Gln149Lys variant was observed as the third most frequent after the DO*HY and DO*JO alleles. Two novel DO*B alleles were identified in the San samples, that is, DO*B‐Ile5Thr and DO*B‐Trp266Arg. Study of K562‐transduced cells showed that compared to the DO*B allele, DO*B‐Ile5Thr was expressed more strongly while DO*B‐Trp266Arg variant was expressed to a lesser extent and was not recognized by MIMA‐123 monoclonal antibodies. CONCLUSION Sequencing analysis showed more allelic combinations in nonpygmoids than in pygmoids with high frequencies of DO*HY, DO*JO, and DO*B‐SH‐Gln149Lys variant alleles. This finding underlines the importance of including DO*HY and DO*JO single‐nucleotide polymorphisms in genotyping tests to improve transfusion safety. Characterization of two novel DO*B alleles highlights the value of testing selected ethnic groups in understanding DO allele diversity.